Analisis Laporan Keuangan Dalam Menilai Kinerja Keuangan Pada Pt. Mandom Indonesia - Popy limpo; Ayu Andini; Rivaldo Tasidjawa; Sartika Hamim (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This study analyzes the financial performance of PT Mandom Tbk. This study aims to find out how the financial performance of PT Mandom Tbk during the 2019 reporting year. This research method is quantitative, namely in the form of secondary data on the annual report of PT. Mandom Indonesia Tbk from the Indonesia Stock Exchange (IDX) website. Liquidity ratio analysis uses current ratio, solvency ratio uses debt to asset ratio and ratio to equity ratio. profitability, activity ratios using return on assets and return on investment, using cash flow ratios and market ratios. Findings of financial performance analysis of PT. Mandom Indonesia Tbk: 1) Profitability ratio using profit margin with medium criteria, return on assets (ROA) in medium criteria and return on equity (ROE) in unfavorable criteria. 2) The liquidity ratio is in very good criteria. 3) The ratio of activity in the criteria is not good. 4) The cash flow ratio is not good enough. 5) The solvency ratio using debt to assets is very high, the criteria are good and the debt to equity ratio is very good. 6) Market ratio in good criteria.